The role of (pro)renin receptor and its soluble form in cardiovascular diseases - Wang, Boyang; Jie, Haipeng; Wang, Shuangxi; Dong, Bo; Zou, Yunzeng (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases are a major cause of death and cause a huge socio-economic burden on health systems worldwide. Unfortunately, the incidence rate of cardiovascular diseases is increasing annually globally, especially in high-income countries. Renin-angiotensin system (RAS) is a major classic therapeutic target for cardiovascular diseases. In addition to circulating RAS, local tissue RAS has been found identified in various tissues and plays a role in tissue inflammation and tissue fibrosis. (Pro) Renin receptor (PRR) has been found as a new member of RAS in 2002. Studies have demonstrated the effects of PRR and its soluble form in local tissue RAS. Moreover, as an important part of H+-ATPase, it also contributes to normal lysosome function and cell survival. Evidently, PRR takes part in the pathogenesis of cardiovascular diseases and may be a potential therapeutic target of cardiovascular diseases. This review focuses on the effects of PRR and its soluble form in physiological state, hypertension, myocardial ischaemia reperfusion injury, heart failure, metabolic cardiomyopathy, and atherosclerosis. Aimed to investigate the possibilities and challenges of PRR and its soluble form as a new therapeutic target in cardiovascular diseases.